Wetlands integrating multidisciplinary concepts - LePage, Ben A. (Springer, 2011)
The science of wetlands and our understanding of these complex ecosystems have improved considerably. The emergence of multidisciplinary strategies is providing new opportunities and innovative approaches to address issues such as climate change and coastal protection. This book, with contributions from 19 specialists from academia, government, and industry, provides a trans-disciplinary approach to the understanding wetlands science, drawing together a wide range of expertise. Topics covered include the physical aspects that shape different wetlands around the world, as well as wetlands ecology, regulation, policy, and related social and economic issues. Featuring contributions from some of the world?s leading wetlands researchers and practitioners, this book provides an invaluable resource for undergraduate and post-graduate training in all aspects of wetlands management, conservation, and construction. It is also a useful auxiliary text for researchers working across disciplines in fields such as wetlands science, law, landscape architecture, environmental engineering, conservation ecology, and related disciplines.